Analisis Motivasi Belajar Peserta Didik pada Kelas VIII di SMP Negeri 27 Makassar - Rifda Nurhikmahwati Arif; Rifda Mardian Arif; Muhammad Arifuddin Jamal; Riski Dewanto (Universitas Tadulako, 2023)
Students cannot achieve the KKM score because of low learning outcomes. There are several factors that cause low learning outcomes, one of which is learning motivation. So in this study aims to determine the level of learning motivation of class VIII students at SMP Negeri 27 Makassar. The research method used is descriptive quantitative which aims to explain the phenomenon systematically. The population in this study was all class VIII and the sample was class VIII.6 using purposive sampling technique. The average learning motivation of students is low during the month of Ramadan due to lack of nutrition and hydration intake, disturbance of sleep patterns, changes in routine, and physical and mental fatigue. While the average learning motivation of students is high before the month of Ramadan because it is caused by time management, physical and mental health and appropriate learning methods.